Characterization of methane oxidation in a simulated landfill cover system by comparing molecular and stable isotope mass balances. (November 2017) - Schulte, Marcel; Jochmann, Maik A.; Gehrke, Tobias; Thom, Andrea; Ricken, Tim; Denecke, Martin; Schmidt, Torsten C.
Highlights: Quantification of bacterial methane oxidation was investigated by isotope analysis. Independent approaches (mass balancing, stoichiometry, and stable isotope analysis). Robust statistical validation of calculated biodegradation in experimental reactor. Thermal imaging to locate bacterial methane oxidation along with isotope analysis. Abstract: Biological methane oxidation may be regarded as a method of aftercare treatment for landfills to reduce climate relevant methane emissions. It is of social and economic interest to estimate the behavior of bacterial methane oxidation in aged landfill covers due to an adequate long-term treatment of the gas emissions. Different approaches assessing methane oxidation in laboratory column studies have been investigated by other authors recently. However, this work represents the first study in which three independent approaches, ((i) mass balance, (ii) stable isotope analysis, and (iii) stoichiometric balance of product (CO2 ) and reactant (CH4 ) by CO2 /CH4 -ratio) have been compared for the estimation of the biodegradation by a robust statistical validation on a rectangular, wide soil column. Additionally, an evaluation by thermal imaging as a potential technique for the localization of the active zone of bacterial methane oxidation has been addressed in connection with stable isotope analysis and CO2 /CH4 -ratios. Although landfills can be considered as open systems the results for stable isotope analysis based on a closed system correlated better with the mass balance than calculations based on an open system. CO2 /CH4 -ratios were also in good agreement with mass balance. In general, highest values for biodegradation were determined from mass balance, followed by CO2 /CH4 -ratio, and stable isotope analysis. The investigated topsoil proved to be very suitable as a potential cover layer by removing up to 99% of methane for CH4 loads of 35–65 g m –2 d –1 that are typical in the aftercare phase of landfills. Finally, data from stable isotope analysis and the CO2 /CH4 -ratios were used to trace microbial activity within the reactor system. It was shown that methane consumption and temperature increase, as a cause of high microbial activity, correlated very well.